Probiotic treatment with specific lactobacilli does not improve an unfavorable vaginal microbiota prior to fertility treatment—A randomized, double-blinded, placebo-controlled trial - Jepsen, Ida E.; Saxtorph, Malene Hviid; Englund, Anne Lis Mikkelsen; Petersen, Kathrine Birch; Wissing, Marie Louise Muff; Hviid, Thomas Vauvert F.; Macklon, Nicholas (Frontiers in Endocrinology, 2022)
Abstract Objective: To investigate whether treatment with proprietary lactobacilli-loaded vaginal capsules improves an unfavorable vaginal microbiome diagnosed using a commercially available test and algorithm. Design: A randomized, double-blinded, placebo-controlled study was conducted in 74 women prior to undergoing fertility treatment at a single university fertility clinic between April 2019 and February 2021. The women were randomly assigned in a 1:1 ratio to receive one vaginal capsule per day for 10 days containing either a culture of more than 108 CFU of Lactobacillus gasseri and more than 108 CFU Lactobacillus rhamnosus (lactobacilli group) or no active ingredient (placebo group). Vaginal swabs for microbiota analysis were taken at enrollment, after treatment and in the cycle following treatment. Participants and methods: Women aged 18–40 years who prior to fertility treatment were diagnosed with an unfavorable vaginal microbiota, characterized by either a low relative load of Lactobacillus or a high proportion of disrupting bacteria using the criteria of the IS-proTM diagnostic system (ARTPred, Amsterdam, the Netherlands), were enrolled in the study. The primary outcome measure was the proportion of women with improvement of the vaginal microbiota after intervention. Results: The vaginal microbiota improved after intervention in 34.2% of all participants (lactobacilli group 28.9%, placebo group 40.0%), with no significant difference in the improvement rate between the lactobacilli and placebo groups, RR = 0.72 (95% CI 0.38–1.38). Conclusion: This study indicates that administering vaginal probiotics may not be an effective means of modulating the vaginal microbiome for clinical purposes in an infertile population. However, a spontaneous improvement rate of 34.2 % over a period of one to three months, confirming the dynamic nature of the vaginal microbiota, indicates that a strategy of postponing further IVF treatment to await microbiota improvement may be relevant in some patients, but further research is needed.